Research on painting layers from barracks no. 12 and no. 15 located on the premises of the State Museum at Majdanek - Klimek, Beata (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2020)
The article presents the results of conservation research on painting studies from barracks no. 12 and no. 15 at the State Museum at Majdanek. The composition of paintings taken from the historic elements of wooden pillars, internal panels and chimneys was tested. The results presented in the article constitute one of the stages of comprehensive research that describes the actual technical condition, the degree of degradation of materials, including painting studies, and the factors influencing the behavior of the barracks serving as a museum facility available to visitors. The results obtained in the research constitute the basis of the necessary information for the development of methods of object conservation. The conducted research and documentation are aimed at preserving for future generations the memorial site of the German Nazi concentration and captive camp in Lublin - a place that witnessed the tragic events of World War II.